(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Liposomes is the most common and well-designed nano-carriers for drug targeting delivery. They have improved therapies for a range of biomedical applications by the help of stabilization therapeutic compounds, to overcome obstacles to cellular and tissue up-take, and improve bio-distribution of drug to target sites in vivo. Objective: The drug is released from liposomes through diffusion technique. The main objective for this drug delivery system was to improve bioavailability and enhance the contact resistance time of drug in the eye. Method: Reverse phase evaporation was used to successfully create liposomes, which were then analyzed for morphology, particle size, drug entrapment effectiveness, and content. Results: The invitro studies shows that this dosage form holds great promise for drug release. As a result, liposomes design showed nearly spherical vesicles. The EE % and DC % could reach up to 88.9% and 92.1% respectively. In vitro release studies show a lipid concentration increase prolong release of drug from liposomes. Conclusion: A dorzolamide sample's melting point, IR scan, and UV scan were all carried out. According to the findings of the studies mentioned above, the medication is called dorzolamide. Following completion of the Preformulation trial, it was discovered that the medication is stable in all PH. In analytical tests, the phosphate buffer pH 5.6, pH 7.4, and pH 6.8 were used to calibrate the dorzolamide curve. It was determined from the investigation that the standard plot was appropriate for use in other analytical studies. Liposome batches demonstrate that integration effectiveness increased as polymer concentration was raised. Scanner electron microscopy was used to characterize the surface of the produced liposomes.